New method for identification of persons using geometry foot outline. (2nd June 2020) - Kafi, Khadidja; Pacha, Adda Ali; Said, Naima Hadj
In this study we try to improve existing recognition rates using plantar surface of foot to extract 19 local geometrical features based on anatomical points and axes, in order to extract informations and relationships required to perform a biometric system for identifying individuals. Before the primary data collection, a pilot study was conducted to assess the precision of stature acquisition and foot measurements. A computer database has been constructed taking measurements from feet pictures of 102 volunteers using the measuring tool in Photofilter. Using the measurements with ±0.38 like error margin and searching through it shows that each foot is unique. This study also showed that each measurement parameter's has an identification percentage and the highest percentages were noted for the parallel and diagonal lengths measurements. To validate our database and our results we tried to study the relation between the stature and some foot measurements using a linear equation of regression.